Novel insights into the genetic and epigenetic paternal contribution to the human embryo (Clinics, 2013)
The integrity of the sperm genome and epigenome are critical for normal embryonic development. The advent of assisted reproductive technology has led to an increased understanding of the role of sperm in fertilization and embryogenesis. During fertilization, the sperm transmits not only nuclear DNA to the oocyte but also activation factor, centrosomes, and a host of messenger RNA and microRNAs. This complex complement of microRNAs and other non-coding RNAs is believed to modify important post-fertilization events. Thus, the health of the sperm genome and epigenome is critical for improving assisted conception rates and the birth of healthy offspring.